CybORGs. Cybernetic Organisms and Cybernetic Organizations - Laura Forlano (Sociologica)
This essay is a short reflection — part memoir, part professional update, and part provocation — that was offered at the 25th anniversary of the Center on Organizational Innovation in November 2024.